2019
DOI: 10.1080/00423114.2019.1626013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wheel-polygonal wear on the dynamic forces within the axle-box bearing of a high-speed train

Abstract: The axle-box bearing is a key component of a high-speed train, providing a safety-critical load path for axial and radial forces transmitted between the wheel-rail interface and the bogie frame. Failure of axle-box bearings can directly affect operational and safety performance of the train, and therefore understanding their operating state is key to predicting potential failure modes and planning maintenance interventions. In this study, a three-dimensional vehicle-track coupled dynamics model, with the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The model additionally contained traction transmission systems for driving the vehicle forward. The motor-car dynamics model was based on a previously published model [42][43][44][45][46]. In the present dynamics model, the kinematic constraints and suspension systems, such as the bump stop, spring stiffness, time-varying mesh stiffness, and the friction force of the gear pair, were implemented by nonlinear elements.…”
Section: Vehicle Suspension Dynamicsmentioning
confidence: 99%
“…The model additionally contained traction transmission systems for driving the vehicle forward. The motor-car dynamics model was based on a previously published model [42][43][44][45][46]. In the present dynamics model, the kinematic constraints and suspension systems, such as the bump stop, spring stiffness, time-varying mesh stiffness, and the friction force of the gear pair, were implemented by nonlinear elements.…”
Section: Vehicle Suspension Dynamicsmentioning
confidence: 99%
“…e primary and secondary suspensions are modeled as equivalent springs and viscous dampers along three translational directions. e details of the vehicle-track coupled dynamics model [20] are shown in Figures 1 and 2.…”
Section: Dynamic Model and Experimental Verificationmentioning
confidence: 99%
“…A great deal of work has been done in the field of railroad vehicles, which focuses on the effect of internal excitation sources on gearboxes [13][14][15][16]. Previous studies [17][18][19] have shown that the wheel polygonization will lead to a surge in vibration response of various components of the vehicle. Wu et al [20,21] used an intelligent algorithm to improve the accuracy of the gearbox model and studied the influence of harmonic traction torque on the vibration and stress of the gearbox.…”
Section: Introductionmentioning
confidence: 99%